PENYELESAIAN KASUS PERZINAHAN SECARA HUKUM ADAT NIAS DI DESA OLANORI - Sadarman Ndruru (Jurnal Panah Hukum, 2023)
Aldutery is one of the cruel that committed by a man and a woman that one of them had got married both of a man as well a women. One of the solution forms of the aldutery case in Olanori village is customary law settlement. At the completion of the case, a penalty was imposed on the perpetrator of adultery in the amount of 5,000,000. (Five millions rupiah) and a pig lima alisi. The society chooses a settlement based on the customary law because they are more concerned with a sense of kinship and a sense of togetherness in which to maintain the cohesiveness of society which has been passed down from generation to generation. In the society, many cases are resolvedaccording to custom which one of them is the case of adultery. The kind of research was used is sociological law research with the descriptive approach. The data was used is the primary data and secondary data. Then, analyzed through qualitative method, and drawing conclusion by deductive. Based on the findings and discussion of the research, can be concluded that the settlement of adultery cases according to Nias customary law in Olanori village is carried out by consensus deliberation through the mediation of the parties carried out by traditional, religious, government (village apparatus) leader by negotiating the problems that happened. If an agreement has reached, the perpetrator of adultery is subject to customary sanctions. Related withthis case, the perpetrators of adultery are subject to financial penalties of 5,000,000. (fivemillion rupiahs), 1 pig (5 alisi). It aimsto prevent a commotion from occurring. The writer suggests so the customary law provisions must be made in writing in the form of village regulations, so that there is certainly of punishment for the people who violate the customary law itself. And, so a village customary institution (LAD)plays an active role on resolving the same case